Assessment of fetal growth in twins: Which method to use?. (November 2022) - Kalafat, Erkan; Khalil, Asma
Abstract: Fetal growth restriction contributes to the excess perinatal mortality and morbidity associated with twin pregnancies. Regular ultrasound monitoring for fetal growth restriction is an essential component of antenatal care of twin gestations. It is accepted that twins have divergent growth trajectories around 28–30 weeks' gestation and are born smaller compared to singletons. Despite this well-established difference in fetal growth, twin pregnancies have been traditionally managed using growth standards developed for singleton pregnancies. Numerous recent studies have demonstrated a strong case supporting the use of twin-specific growth standards, but clinical implementation has been lacking. In this paper, we will review the evidence on factors affecting fetal growth, the rationale for twin-specific reference charts, clinical evidence for their use, and future direction of research. Applying singleton growth standards to twin pregnancies inflates the abnormal growth rate, and recent clinical evidence from several studies suggests that they are too stringent for classification of twins. The association of adverse perinatal and maternal outcomes such as perinatal death, preterm birth, neonatal care unit admission, hypertensive disorders of pregnancy, and composite neonatal morbidity is stronger when classification is made using twin-specific standards compared to singletons. Highlights: Fetal growth restriction is associated with increased perinatal mortality and morbidity in twin pregnancies. Twins have divergent growth trajectories around 28-30 weeks' gestation and are born smaller compared to singletons. Recent studies present a strong case supporting the use of twin-specific charts in the assessment of fetal growth. The use of singleton charts to assess the growth in twin pregnancies overdiagnose abnormal growth rate. The association of adverse perinatal and maternal outcomes is stronger when classification is made using twin-specific compared to singleton charts.